Stage-Specific Effects of Candidate Heterochronic Genes on Variation in Developmental Time along an Altitudinal Cline of Drosophila melanogaster. - Mensch, J.; Carreira, V.; Lavagnino, N.; Goenaga, J.; Folguera, G.; Hasson, E.; Fanara, J.J. (PLoS ONE, 2010)
Previously, we have shown there is clinal variation for egg-to-adult developmental time along geographic gradients in Drosophila melanogaster. Further, we also have identified mutations in genes involved in metabolic and neurogenic pathways that affect development time (heterochronic genes). However, we do not know whether these loci affect variation in developmental time in natural populations.Here, we constructed second chromosome substitution lines from natural populations of Drosophila melanogaster from an altitudinal cline, and measured egg-adult development time for each line. We found not only a large amount of genetic variation for developmental time, but also positive associations of the development time with thermal amplitude and altitude. We performed genetic complementation tests using substitution lines with the longest and shortest developmental times and heterochronic mutations. We identified segregating variation for neurogenic and metabolic genes that largely affected the duration of the larval stages but had no impact on the timing of metamorphosis.Altitudinal clinal variation in developmental time for natural chromosome substitution lines provides a unique opportunity to dissect the response of heterochronic genes to environmental gradients. Ontogenetic stage-specific variation in invected, mastermind, cricklet and CG14591 may affect natural variation in development time and thermal evolution.